2008
DOI: 10.1002/dc.20730
|View full text |Cite
|
Sign up to set email alerts
|

Papillary carcinoma with nodular fasciitis‐like stroma—A case report in pregnancy

Abstract: We report a case of Papillary carcinoma with nodular fasciitis-like stroma that is a rare variant of Papillary carcinoma characterized by a prominent stromal cell proliferation that causes difficulties in cytologic and histologic diagnosis. The patient was a 34-year-old woman, pregnant, presented with a 1-year history of a growing mass in neck, dysphagia, and hoarseness. Physical examination revealed a firm nodular mass in thyroid gland. The fine needle aspiration biopsy specimen contained, besides diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Although the clinical features of this tumor have not been clarified, they may be similar to a classical variant of PTC in previous reports [1][2][3][4][5][6][7][8][9]. In this variant, the size and extension of the neoplastic epithelial component is important to determine prognosis [7].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although the clinical features of this tumor have not been clarified, they may be similar to a classical variant of PTC in previous reports [1][2][3][4][5][6][7][8][9]. In this variant, the size and extension of the neoplastic epithelial component is important to determine prognosis [7].…”
Section: Discussionmentioning
confidence: 83%
“…In this variant, the size and extension of the neoplastic epithelial component is important to determine prognosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed an aberrant immunohistochemical expression of β-catenin in the nucleus and cytoplasm of mesenchymal cells, but the molecular cause for the activation of the Wnt signaling pathway in these tumors remains unknown. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Aberrant nuclear accumulation of β-catenin is reported in different neoplastic and reactive conditions and is related to direct or indirect alterations of the Wnt/β-catenin pathway. 19 Among thyroid carcinomas, cytoplasmic and nuclear accumulation of β-catenin has been reported only in the cribriform-morular variant, which occurs sporadically or as an extra-intestinal manifestation of the familial adenomatous polyposis syndrome; in this case, it is associated with the presence in the follicular cells of activating somatic mutations in CTNNB1, the gene encoding β-catenin.…”
mentioning
confidence: 99%
“…3,4 To the best of our knowledge, only 20 cases have been reported in the English literature. [5][6][7] Th e age at presentation ranges from 20 to 82 years, with a mean of 44.5 years (our patient was 46 years old); a female preponderance has been observed, with a female-to-male ratio of 3:1. 6 No racial predilection has been observed.…”
Section: Discussionmentioning
confidence: 90%